2013
DOI: 10.2478/pjs-2013-0030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of inflammatory markers as predictors of hospital stay and unplanned readmission after colorectal surgery

Abstract: Hospital length of stay (LOS) and readmissions continue to be expensive and unexpected events following colorectal surgery (CRS) whether patients follow enhanced recovery pathways or traditional care. Predictors of these adverse events could facilitate identification and optimization of CRS patients. the aim of the study was to examine the impact of white blood cell count (WBC) and C-reactive protein (CRP) levels as predictors of delayed recovery or hospital readmission following CRS. material and methods. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Early diagnosis is therefore essential for optimum management of this complication. Exclusion of a leak early can result in a shorter hospital stay . Desirable qualities of a good clinical diagnostic tool should include being easily accessible, cost effective and easily interpretable .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early diagnosis is therefore essential for optimum management of this complication. Exclusion of a leak early can result in a shorter hospital stay . Desirable qualities of a good clinical diagnostic tool should include being easily accessible, cost effective and easily interpretable .…”
Section: Introductionmentioning
confidence: 99%
“…Exclusion of a leak early can result in a shorter hospital stay. 4 Desirable qualities of a good clinical diagnostic tool should include being easily accessible, cost effective and easily interpretable. 5 C-reactive protein (CRP) has been a promising serum indicator for the detection of post-operative anastomotic leaks in colorectal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…There have been other studies, specifi cally regarding C-reactive protein (CRP) to try and achieve similar predictive models after colectomy. Krapta et al [15]. Demonstrated that non-elevation of CRP was able to accurately predict shorter length of hospital stay (p<0.01) with average CRP values of 6.3 in those with a LOS < 3 days, vs 11.7 in those with LOS > 4 days.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with our other findings on reducing the level of inflammation and the severity of the disease in the ICU. Similarly, a study of 193 patients who underwent colorectal surgery found that lower hs‐CRP levels on the second postoperative day (POD2) were associated with a shorter hospital LOS (Krpata et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%